2021
DOI: 10.3390/en14144299
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Pandemic on Vehicle Traffic and Roadside Environmental Pollution: Rzeszow City as a Case Study

Abstract: The development of the COVID-19 pandemic and the related lockdown had a major impact on vehicle traffic in cities. Based on available data from the selected city of Rzeszow, Poland, it was decided to assess changes in vehicle traffic and the impact of these changes on roadside environmental pollution. As part of the research, data from the first half of 2020 regarding vehicle traffic on selected streets of the city and on the city’s inlet routes were analyzed. For the selected road sections, changes in hourly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Results of this study revealed there was a reduction in traffic volume level in most districts such as Kelapa Gading (8%), Kebon Jeruk (1%), and Jagakarsa (0.8%) during the LSSR period ( Figure 2 ). The decrease in vehicle traffic was also recorded in the Rzeszow city of Poland which was found in the first phase of the pandemic from March to April 2020 ( Smieszek et al, 2021 ). The other studies also revealed the reducing traffic volume and industrial activities during the COVID-19 lockdown period which then were associated with the changes in air pollutants levels ( Nakada & Urban, 2020 ; Selvam et al, 2020 ; Tobías et al, 2020 ).…”
Section: Resultsmentioning
confidence: 85%
“…Results of this study revealed there was a reduction in traffic volume level in most districts such as Kelapa Gading (8%), Kebon Jeruk (1%), and Jagakarsa (0.8%) during the LSSR period ( Figure 2 ). The decrease in vehicle traffic was also recorded in the Rzeszow city of Poland which was found in the first phase of the pandemic from March to April 2020 ( Smieszek et al, 2021 ). The other studies also revealed the reducing traffic volume and industrial activities during the COVID-19 lockdown period which then were associated with the changes in air pollutants levels ( Nakada & Urban, 2020 ; Selvam et al, 2020 ; Tobías et al, 2020 ).…”
Section: Resultsmentioning
confidence: 85%
“…Each vehicle type involved in the simulation must have defined instantaneous emission parameters [49]. The breakdown of passenger cars by fuel type was as follows: 65% petrol, 30% diesel and 5% LPG, as stated by the authors of [52,53]. At first, we modelled the actual dimensions and design of the intersection (number of lanes on each arm) (Figure 3).…”
Section: Modelling Methodology and Simulationmentioning
confidence: 99%
“…Compared to data before the pandemic, passenger transport by public transport in the city of Rzeszow decreased approximately twice. The impact of the pandemic itself on changes in traffic and transport has been described in the literature [16][17]. With a significant decrease in passenger transport, an interesting question is what the data on energy consumption in traffic look like.…”
Section: Characteristics Of the Bus Operating Indicators On The Studi...mentioning
confidence: 99%